(untitled) (Bangladesh Journal of Animal Science, 2017)
The study aimed to examine the feeding, management, income and livelihood improvement through goat rearing in Mymensingh district. The study was conducted at different unions namely Gazirvita, Koichapur and Norail of Haluaghat Upazila in Mymensingh district. Total 45 respondents were randomly selected from three unions where 15 from each union. The respondents were classified into three distinct groups. The farmers belonged to Group-G, who lives in Gazirvita union, Group-K, who lives in Koichapur union and Group-N, belonged to the farmers who lives in Norail union. The period of data collection was from April to June, 2011. The farmers families were poorest of the poor and illiterate. The annual total cost of production of Black Bengal goat was Tk. 2154, while gross return and net return per household were Tk. 4296 and Tk. 2142, respectively. Educational status, employment for men, employment for women, social dignity and social acceptance were increased at 35, 24, 58, 26 and 23% through goat rearing in the study area. The result clearly indicates that livelihood increases dramatically through goat rearing in the study area. Bang. J. Anim. Sci. 2017. 46 (1): 29-34